2022
DOI: 10.1177/10790632221120381
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Perpetrator and Solo-Offender Sexual Assaults Between Strangers: Differences and Predictive Variables

Abstract: Multiple-perpetrator rape is an under-studied topic, but there has been a recent increase in studies on the differences between multiple-perpetrator sexual offenses and the ones perpetrated by solo offenders. This study aims to have a deeper understanding of the differences between multiple-perpetrator and solo-offender sexual assaults committed by strangers, from a sample of 400 sexual aggressions reported to the Spanish police in 2010. Differences were explored on variables related to characteristics of perp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
(146 reference statements)
1
0
0
Order By: Relevance
“…In terms of prior convictions, our results are in line with Park and Kim (2016) who found that lone perpetrators had more prior convictions than duos and, that duos had more than groups of three or more perpetrators. This conclusion is also consistent with previous studies finding that lone perpetrators are more specialised and plan their sexual assaults more than MPR offenders (da Silva et al, 2018; Gimenez‐Salinas et al, 2022; Harkins & Dixon, 2010). da Silva et al (2018) revealed that 92% of MPR perpetrators stated that they had not planned the sexual assault previously.…”
Section: Discussionsupporting
confidence: 92%
“…In terms of prior convictions, our results are in line with Park and Kim (2016) who found that lone perpetrators had more prior convictions than duos and, that duos had more than groups of three or more perpetrators. This conclusion is also consistent with previous studies finding that lone perpetrators are more specialised and plan their sexual assaults more than MPR offenders (da Silva et al, 2018; Gimenez‐Salinas et al, 2022; Harkins & Dixon, 2010). da Silva et al (2018) revealed that 92% of MPR perpetrators stated that they had not planned the sexual assault previously.…”
Section: Discussionsupporting
confidence: 92%